Retrospective Analysis of Rechallenge with Ipilimumab in Patients with Metastatic Melanoma - A. A. Formozo; J. R. Gomes; R. A. Schmerling; A. C. Buzaid (Journal of Skin Cancer)
Background. Checkpoint inhibitors are effective in the treatment of several types of cancer, either being used separately or in combination. Ipilimumab pioneered the treatment of metastatic melanoma, and nowadays, it has been used more frequently in combination with anti-PD-1. Since the development of anti-PD1 for melanoma, rechallenge with ipilimumab has not been considered, although its use was considered in early trials. Cases. In this study, we analyzed 22 patients with metastatic melanoma who had benefited from the first treatment with ipilimumab, but eventually had progressive disease. They received ipilimumab at the same dose as the first treatment. Most of the patients received the second course after six months or more from the first treatment with ipilimumab. The median progression-free survival (mPFS) of the treatment with ipilimumab was 8.9 months, and the median progression-free survival of the second course was 6.3 months. Conclusion. There are limited data on rechallenge with ipilimumab addressing progression-free survival (PFS). In our analysis, twenty-two patients treated with a second course of ipilimumab were analyzed and most of them had a significant benefit. Despite the current alternatives for salvage therapies, rechallenging with ipilimumab might be an alternative to be considered in patients who had initial benefit.